Depression and cardiovascular disease in women: is there a common immunological basis? A theoretical synthesis. (April 2014) - Wright, Lauren; Simpson, William; Van Lieshout, Ryan J.; Steiner, Meir
Clinical studies have established an inherent comorbidity between depression and the development of cardiovascular disease (CVD). Furthermore, this comorbidity seems to be more amplified in women than in men. To further investigate this comorbidity, a thorough literature review was conducted on studies from 1992 to date. The PubMed database was accessed using the keywords: cardiovascular disease, inflammation, depression, and sex differences. Both human and animal studies were considered. This review takes the standpoint that depression and CVD are both inflammatory disorders, and that their co-occurrence may be related to how the hypothalamic–pituitary–adrenal axis, serotonergic transmission and circulation, and the renin–angiotensin–aldosterone system via angiotensin II are affected by the excess secretion of proinflammatory cytokines. More recently, preliminary research attributes this systemic inflammation to a global deficiency in CD4+CD25+FOXP3 regulatory T cells. 17-β estradiol and progesterone mediated modulation of cytokine secretion may partially explain the sex differences observed. These hormones and reproductive events associated with hormonal fluctuations are discussed in depth, including the analysis of perinatal models of depression and CVD, including preeclampsia. However, as evidenced by this review, there is a need for mechanistic research in humans to truly understand the nature and directionality of the relationship between depression and CVD.